Tapping the potential of quantum dots for personalized oncology: current status and future perspectives. (March 2012) - Chen, Chuang; Peng, Jun; Sun, Sheng-Rong; Peng, Chun-Wei; Li, Yan; Pang, Dai-Wen
Cancer is one of the most serious health threats worldwide. Personalized oncology holds potential for future cancer care in clinical practice, where each patient could be delivered individualized medicine on the basis of key biological features of an individual tumor. One of the most urgent problems is to develop novel approaches that incorporate the increasing molecular information into the understanding of cancer biological behaviors for personalized oncology. Quantum dots are a heterogeneous class of engineered fluorescent nanoparticles with unique optical and chemical properties, which make them promising platforms for biomedical applications. With the unique optical properties, the utilization of quantum dot-based nanotechnology has been expanded into a wide variety of attractive biomedical applications for cancer diagnosis, monitoring, pathogenesis, treatment, molecular pathology and heterogeneity in combination with cancer biomarkers. Here, we focus on the clinical application of quantum dot-based nanotechnology in personalized oncology, covering topics on individualized cancer diagnosis and treatment by in vitro and in vivo molecular imaging technologies, and in-depth understanding of the biological behaviors of tumors from a nanotechnology perspective. In addition, the major challenges in translating quantum dot-based nanotechnology into clinical application and promising future directions in personalized oncology are also discussed.